Role of the dimensions of administrative development in realizing the excellent performance of workers in the executive committees at the General Sport Federation in the Syrian Arab Republic (Journal of Hama University, 2022)
The aim of the research is to find out the level of exposure to bullying behavior among a sample of workers with motor disabilities in government departments and the differences between them according to the variables (age, gender, number of years of service). The sample consisted of (30) male and female workers with disabilities, and they were divided into groups according to gender within two groups (8) females and (22) males, as well as within three age groups, which are (25-20 years), (30-26 years) and (31 years and over). To achieve the aims of the research, the researcher prepared a scale to measure the level of bullying behavior among a sample of workers in government departments with disabilities. The results of the research indicated that there are statistically significant differences between the average scores of workers with disabilities on the study tool at the level (0.05) according to the younger age group, and also that there are no statistically significant differences between. The average of the study sample on the scale of the study tool at the level (0.05) according to the gender variable, with statistically significant differences in physical and material bullying in favor of males, and in emotional and social bullying in favor of females.